Enteric Myocarditis: A Case Report - Mahmud, Kawkab; Musa, AKM; Ahmed, AKM Shaheen; Nazimuddin, Khwaja; Sarker, RSC (Ibrahim Medical College Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Enteric fever commonly causes fatality from abdominal complications or toxemia but it can also cause death from complications of myocarditis albeit rarely. In September, 2005 a 22 year old man was admitted in BIRDEM with the features of pneumonia. Later on, the patient developed acute left ventricular failure and ultimately diagnosed as a case of drug resistant enteric fever with myocarditis Ibrahim Med. Coll. J. 2007; 1(1): 34-37 Key words: Enteric fever; abdominal complications doi: 10.3329/imcj.v1i1.2893